Search for QCD instanton-induced processes at HERA in the high-Q2 domain - Andreev, Vladimir; Bolz, Arthur; Huber, Florian; Sauter, Michel David; Schöning, André (The European physical journal. C, Particles and fields, 2016)
Signals of QCD instanton-induced processes are searched for in neutral current deep-inelastic scattering at the electron-proton collider HERA in the kinematic region defined by the Bjorken-scaling variable